2007
DOI: 10.5927/jjjd1991.17.29
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Evaluation of Morphological Asymmetry of Maxillofacial Complex in Patients Showing Mandibular Prognathism with Facial Asymmetry

Abstract: The present study was designed to three-dimensionally evaluate the morphological asymmetry of maxillofacial complexes such as the maxilla and the mandible, and the state of the maxillary and mandibular deviation in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regarding the use of 3-D CT imaging for analysis, one report notes that whereas cases with remarkable asymmetry in the maxilla are rare, as is dispersion between cases, there are also cases in which the maxilla is in a location asymmetrical to the skull. It was also noted Three-dimensional Analysis that in the mandible, in most cases, asymmetry was found in the mandible itself, but no large difference was observed between cases 31) . Measurement of horizontal (X) change in distance between T1 and T2 in the maxilla in the present study revealed values of 1.0 mm for U6TC and 0.2 mm for ANS, indicating only minimal change.…”
Section: Distance Measurement 1) T1 and T2 Assessmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Regarding the use of 3-D CT imaging for analysis, one report notes that whereas cases with remarkable asymmetry in the maxilla are rare, as is dispersion between cases, there are also cases in which the maxilla is in a location asymmetrical to the skull. It was also noted Three-dimensional Analysis that in the mandible, in most cases, asymmetry was found in the mandible itself, but no large difference was observed between cases 31) . Measurement of horizontal (X) change in distance between T1 and T2 in the maxilla in the present study revealed values of 1.0 mm for U6TC and 0.2 mm for ANS, indicating only minimal change.…”
Section: Distance Measurement 1) T1 and T2 Assessmentmentioning
confidence: 89%
“…This agrees with the tendency for the mandible to move more than the maxilla. It has been noted that Me in the mandible is the furthest reference point from the upper face, and that even a minimal deviation in the lower face from the upper-or mid-face is easily noticed 31) . Indeed, a significant difference was found in ME between T1 and T2 in the present study (p=0.021).…”
Section: Distance Measurement 1) T1 and T2 Assessmentmentioning
confidence: 99%
“…Jaw deviation usually involves both the maxilla and mandible. To date, however, various types of jaw deviation have been relatively challenging to visualize using three-dimensional (3D) techniques [ 5 ]. It is reported that two-dimensional cephalometric prediction such as STO (Surgical Treatment Objectives) [ 6 ] is still popular but not proper to precisely analyze remarkable facial symmetric cases.…”
Section: Introductionmentioning
confidence: 99%